2022
DOI: 10.3389/fnana.2022.1054849
|View full text |Cite
|
Sign up to set email alerts
|

Alpha retinal ganglion cells in pigmented mice retina: number and distribution

Abstract: Purpose: To identify and characterize numerically and topographically the population of alpha retinal ganglion cells (αRGCs) and their subtypes, the sustained-response ON-center αRGCs (ONs-αRGCs), which correspond to the type 4 intrinsically photosensitive RGCs (M4-ipRGCs), the transient-response ON-center αRGCs (ONt-αRGCs), the sustained-response OFF-center αRGCs (OFFs-αRGCs), and the transient-response OFF-center αRGCs (OFFt-αRGCs) in the adult pigmented mouse retina.Methods: The αRGC population and its subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 76 publications
2
13
0
Order By: Relevance
“…However, it is unclear how sensitive they are to label or recombine loxP -flanked cassettes in M4-M6s. Surveying the entire retina for M4s using the Opn4 cre(DSO ) ; Ai14 (tdTomato+ SMI32+, Fig 5a-c), we found 722 ± 58 cells, representing ∼1.44% of all RGCs similar to the reported ∼840 Alpha ON-sustained cells per retina 55 . However, with no alternative means to label the M5 and M6 population comprehensively and independently of Opn4 cre(DSO ) , it remains unclear if this, or any line captures the majority of these low melanopsin-expressing populations.…”
Section: Discussionsupporting
confidence: 73%
“…However, it is unclear how sensitive they are to label or recombine loxP -flanked cassettes in M4-M6s. Surveying the entire retina for M4s using the Opn4 cre(DSO ) ; Ai14 (tdTomato+ SMI32+, Fig 5a-c), we found 722 ± 58 cells, representing ∼1.44% of all RGCs similar to the reported ∼840 Alpha ON-sustained cells per retina 55 . However, with no alternative means to label the M5 and M6 population comprehensively and independently of Opn4 cre(DSO ) , it remains unclear if this, or any line captures the majority of these low melanopsin-expressing populations.…”
Section: Discussionsupporting
confidence: 73%
“…Analysis of adult retinal flat mounts stained with SMI-32 further showed that due to a significant reduction in SMI-32 + α-RGCs upon Pkn1 knockout ( Figure 4 b–d), fewer RGC axons left the retina at the optic nerve head. The fact that the pan-RGC marker RBPMS did not reveal differences in RGC numbers is likely explained by the much lower abundance of α-RGCs (~5% of all RGCs) compared to the total amount of RGCs [ 18 ]. SMI-32 + α-RGC axons of Pkn1 −/− animals did not show pathfinding defects to the optic nerve ( Figure 4 e) or optic tract ( Figure 4 f).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Md -CiRGCs exhibited axon growth-enhancing genes ( Extended data Fig. 15b ) and 90% of BRN3A + Md- CiRGCs express the αRGC marker SPP1, a subtype, possess a greater propensity to regenerate their axons after axotomy 51, 52 . These results suggest a pro-regenerative state in CiRGCs, that support its regenerative ability in mice in vivo studies.…”
Section: Discussionmentioning
confidence: 99%